Association between foot morphology and dynamic knee valgus during single leg squats in recreational male football players: a cross-sectional study - Kumar Purushothaman, Vinosh; Noorul Uyoon, Ahmed Ibrahim Didi; Subramaniam, Ambusam; Subbarayalu, Arun Vijay; Prabaharan, Sivasankar; Ameer, Mariam; Sheriff, Ajmal; Prathap, Arun; Rubavathi Marimuthu, Palanivel (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. This study examines the relationship between foot morphology, foot type, and dynamic knee valgus in male football players during single-leg squats using biomechanical analyses.Methods. A cross-sectional study design was adopted. Male football players (n = 151) aged between 18 and 30 years belonging to three Malaysian football clubs were recruited. Of these participants, foot type, single-leg squat (SLS) performance, knee alignment using knee frontal plane projection angle (FPPA), and other measures of foot morphology were recorded, including foot length, foot width, truncated foot length, and navicular height. Chi-square tests were used to examine the association between foot type, SLS, and knee alignment. Bipoint serial correlations were used to determine the relationship between foot morphology, SLS, and knee alignment.Results. A significant association was found between foot type and SLS (p < 0.05). During the SLSs, only navicular height (rpb = 0.154, n = 151, p < 0.05) and dorsal height (rpb = 0.144, n = 151, p < 0.05) showed a statistically significant connection in the dominant leg. In contrast, only navicular height in the non-dominant leg (rpb = 0.169, n = 151, p < 0.05) showed a sig-nificant correlation with SLSs.Conclusions. This study established a strong link between foot type and SLS in football players. Specifically, a statistically significant association between navicular and dorsal height in the dominant leg and navicular height in the non-dominant leg. This study emphasises the significance of foot morphology and the dynamic evaluation of knee valgus during functional movements.
Keywords: foot anatomy; health risk; football; knee kinematics; athletic injury; unilateral squat